Hypoglycaemic Status in Low Birth Weight Neonates During First 48 Hours of Life (Journal of Armed Forces Medical College, Bangladesh, 2014)
Introduction: In developing countries more than 90% infants are born with low birth weight (LBW). In Bangladesh the incidence is about 30%. Newborn baby has got a definite difference in metabolic profile from the adult; this difference is much more pronounced in case of LBW newborn. Infants born prematurely or following intrauterine malnutrition may develop abnormally low plasma glucose concentration for a prolonged period as a result of the failure to adapt a metabolic and endocrine response.Glucose is an essential nutrient for the brain. Abnormally low levels (hypoglycaemia) can cause encephalopathy and have the potential to produce long-term neurological injury. Adequate knowledge about neonatal physiology is important in the management of LBW neonates in the neonatal nursery specially in the first 48 hours of life as most of the neonatal deaths occur in this critical period of time. Objectives: To evaluate the clinical features of hypoglycaemic low birth weight (LBW) neonates in the first 48 hours of life. Methods: This cross-sectional study was conducted on 56 LBW neonates in the inpatient departments of Paediatrics and Obstetrics of Combined Military Hospital (CMH), Dhaka between 15th September 2010 to 14th March 2011. LBW (Weight